The Povarov Reaction as a Versatile Strategy for the Preparation of 1, 2, 3, 4-Tetrahydroquinoline Derivatives: An Overview - S. Bello Forero, Josue; Jones Junior, Joel; M. da Silva, Flavia (Current Organic Synthesis, 2016)
Tetrahydroquinoline (THQ) subunits are present in many natural products and biologically active agents, such as anti-viral, anti-biotic, and anti-tumour medications. The synthesis of THQs is described extensively in literature due to the search for a general, simple, efficient and low-cost preparation method. The retrosynthetic analysis for THQ synthesis has many strategies involving the formation of one or two C-C or C-N bonds. In 1963, Povarov et al. published two studies named “A new type of diene condensation reaction” and “Reaction of benzylideneaniline with some unsaturated compounds
Keywords: Dienophile